Do the effects of nonverbal behaviour on team outcome confidence in team sports depend on the availability of additional performance information? - Seiler, Kirstin; Schweizer, Geoffrey; Seiler, Roland (Psychology of sport and exercise, 2018)
The aim of the present research is to investigate whether the effects of nonverbal behaviour (NVB) on team outcome confidence in sports decrease when additional information on players' performance is provided. In three experiments using video footage of football players, we examined the effects of both NVB and performance information on team outcome confidence. When no additional performance-related information was given, team outcome confidence was significantly influenced by NVB (Experiment 1). When performance-related information was added, the effect of NVB remained large, independent of how strong information distinguished between low- and high-performance players (Experiments 2 and 3). In line with previous research, our results suggest that NVB has an important impact on a team's outcome confidence even when additional performance-related information is available.